Attachment and Jealousy: Understanding the Dynamic Experience of Jealousy Using the Response Escalation Paradigm. (December 2018) - Huelsnitz, Chloe O.; Farrell, Allison K.; Simpson, Jeffry A.; Griskevicius, Vladas; Szepsenwol, Ohad
Jealousy is a complex, dynamic experience that unfolds over time in relationship-threatening situations. Prior research has used retrospective reports that cannot disentangle initial levels and change in jealousy in response to escalating threat. In three studies, we examined responses to the Response Escalation Paradigm (REP)—a 5-stage hypothetical scenario in which individuals are exposed to increasing levels of relationship threat—as a function of attachment orientations. Highly anxious individuals exhibited hypervigilant, slow escalation response patterns, interfered earlier in the REP, felt more jealousy, sadness, and worry when they interfered, and wanted to engage in more vigilant, destructive, and passive behaviors aimed at their partner. Highly avoidant individuals felt more anger when they interfered in the REP and wanted to engage in more partner-focused, destructive behaviors. The REP offers a dynamic method for inducing and examining jealousy and introduces a novel approach to studying other emotional experiences.